PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT ARTOTEL CASA HANGTUAH - Trio Setia Anggoro; Hafis Laksmana Nur Aldy (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine whether there positive and is a significant influence between Work Discipline and Physical Work Environment either partially or simultaneously on Employee Performance at PT Artotel Casa Hangtuah. This study uses a quantitative research method with an Associative approach where the data obtained is in the form of a questionnaire processed using the SPSS version 26 application, the results are There is an influence of Work Discipline on Employee Performance at PT Artotel Casa Hangtuah. Shown by the regression equation Y = 3.630 + 0.887 X1, above the correlation coefficient (R) value of 0.771 which means the coefficient between variables X1 and Y is strong, The t-value of the Work Discipline variable is 8.729 greater than the t-table value of 2.00758 with a significance level of 0.0 less than 0.05, it can be interpreted that Ha1 is accepted and H01 is rejected, so it can be concluded that partially Work Discipline has a positive and significant effect on employee performance, There is an influence of the Physical Work Environment on Employee Performance at PT Artotel Casa Hangtuah shown by the regression equation Y = 16.452 + 0.638 X2, the correlation coefficient (R) value of 0.720 which means the coefficient between variables X2 and Y is strong. The t-value of the Physical Work Environment variable is 7.482 greater than the t-table of 2.00758 with a significant level of 0 less than 0.05, it can be interpreted that Ha2 is accepted and H01 is rejected. So it can be concluded partially that the Physical Work Environment has a positive and significant effect on Employee Performance, There is an influence of Work Discipline and Physical Work Environment on Employee Performance at PT Artotel Casa Hangtuah. Proven by the regression equation Y = 2.849 + 0.602 X1 + 0.322 X2, the correlation coefficient (R) value is 0.815 which means the coefficient between the variables of Work Discipline and Physical Work Environment on Employee Performance is very strong, it is known that the value of the determination coefficient (KD) = (R2) x 100% is obtained from R, namely KD = 0.665 x 100% = 66.5% while the remaining 33.5% (100% -66.5%) is the influence of other factors that are not studied, it is known that F count is 50.547 and the significance value is 0 while the F table value is 3.18 So it can be concluded that F count> F table (50.547> 3.18) and significance <0.05 (0 <0.05), then Ha3 is accepted, so it can be concluded that Work Discipline and Physical Work Environment together have an effect on Employee Performance